2021
DOI: 10.1507/endocrj.ej20-0286
|View full text |Cite
|
Sign up to set email alerts
|

The effects and safety of activators of glucokinase <i>versus</i> placebo in patients with type 2 diabetes mellitus: a systematic review and meta-analysis

Abstract: We undertook a systematic review and meta-analysis to assess the effects and safety of activators of glucokinase (GKAs) in patients with type 2 diabetes mellitus (T2DM). 11 RCTs, including 2,429 participants, are enrolled in our study. According to different doses, we divided the studies into 3 groups: low-dose group, medium-dose group and high-dose group for subgroup analysis. There were decreases of HbA1c in all dose group (WMD =-0.27, 95%CI (-0.51~-0.03), Z = 2.17, p = 0.03; WMD =-0.37, 95%CI (-0.58~-0.16),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Mean glucose was 10¢680 mmol/L (SD 1¢990) with placebo and 10¢820 mmol/L (2¢670), 10¢020 mmol/L (2¢010), and 8¢700 mmol/L (2¢140) with three dose levels of PB-201. TIR increased as the dose of PB-201 increased, and TIRs in those given 100+50 and 100+100 mg were higher than that with placebo (mean TIR, 49¢380% [SD 27], 49¢210% [27], 56¢130% [25], and 63¢330% [20] with placebo and the three dose levels of PB-201, respectively; figure 3B). Only 0¢310%, 0, 0¢070%, and 4¢600% of time on average respectively were found to be TBR (<3¢9 mmol/L), indicating low frequencies of hypoglycaemia with both placebo and PB-201; the corresponding percentage of TBR (<3¢0 mmol/L) was 0 with all four regimens.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mean glucose was 10¢680 mmol/L (SD 1¢990) with placebo and 10¢820 mmol/L (2¢670), 10¢020 mmol/L (2¢010), and 8¢700 mmol/L (2¢140) with three dose levels of PB-201. TIR increased as the dose of PB-201 increased, and TIRs in those given 100+50 and 100+100 mg were higher than that with placebo (mean TIR, 49¢380% [SD 27], 49¢210% [27], 56¢130% [25], and 63¢330% [20] with placebo and the three dose levels of PB-201, respectively; figure 3B). Only 0¢310%, 0, 0¢070%, and 4¢600% of time on average respectively were found to be TBR (<3¢9 mmol/L), indicating low frequencies of hypoglycaemia with both placebo and PB-201; the corresponding percentage of TBR (<3¢0 mmol/L) was 0 with all four regimens.…”
Section: Resultsmentioning
confidence: 99%
“…In two phase 2 clinical trials comparing PB-201, placebo, and active comparators as an add-on to metformin in patients with type 2 diabetes, hypoglycaemia occurred in 3¢0% (12/405) of patients with PB-201, 34¢4% (21/61) with glimepiride, 1¢8% (1/55) with sitagliptin, and 2¢5% (3/118) with placebo; all resolved with oral carbohydrates [10]. In comparison, hypoglycaemia was reported at an incidence rate ranging from 0¢6% (1/169) to 33¢8% (68/201) with other GKAs [27]. In a phase 2 trial in Chinese patients with type 2 diabetes, hypoglycaemia was reported in 5¢4% (11/205) of patients with dorzagliatin [8].…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation